Two-Point Left Ventricle Pacing and Cardiac Computed Tomography - Rafal Mlynarski; Agnieszka Mlynarska; Eugeniusz Pilat; Rafal Gardas; Jacek Wilczek; Maciej Sosnowski (Case Reports in Cardiology)
Endocardial leads can potentially cause problems during coronary vessels visualization in multislice computed tomography (MSCT) due to a large number of artifacts. Based on presented case, we conclude that it is possible to perform MSCT of coronary arteries and leads visualization despite coexistence of four endocardial leads.